Fenologia, biologia reprodutiva e componentes de rendimento de Acca sellowiana no sudoeste do Paraná - Turra, Eliza Luana Charneski (2017)
Acca sellowiana is a fruit species belonging to the Myrtaceae botanic family, native from southern Brazil and northern Uruguay, popularly known in Brazil as goiabeiraserrana, araçá-grande, goiabeira-do-mato and feijoa. In Brazil cultivars have been already developed for high altitude conditions in Santa Catarina state and there is a participatory breeding program of the species in the high altitude region of Rio Grande do Sul state, where the species is adapted to the conditions of that climate. Adaptation of superior genotypes to the southwestern region of Paraná state is unknown, although the species is native to the higher altitude regions of the state. In this context, the objective of this research was to analyze phenological behavior, reproductive biology (pollen germination and autoincompatibility), fruit growth, and yield components of a segregating A. sellowiana population, in order to study the behavior of these species in the region, as well as to select promising genotypes adapted to the region. The experiments were carried out in Dois Vizinhos and Pato Branco, Paraná state from 2014 to 2017, with progenies of five crosses originating from diallel crosses between four elite matrices of the Germoplasma Active Bank of the species: Alcântara, Helena, Mattos e Nonante varieties. The spacing was 4.5 x 3.0m, with experimental arrangement in randomized blocks, containing four replications and each experimental plot being composed of three plants. The evaluated parameters were the phenology of flowering, pollen viability, self-incompatibility, fruit set, fruit growth and productivity. The phenological data were tabulated and presented in graphical form correlated with local meteorological data. The reproductive biology (through manual self-pollination, manual cross-pollination, and open pollination) was also determined, and pollen viability was evaluated by in vitro germination test. In the reproductive phase, productivity, fruit characteristics (size, weight, pulp yield, thickness, soluble solids, color, roughness, and sensory evaluation), maturation and precocity were evaluated. The continuous data collected were submitted to variance analysis and the discrete data to frequency analysis. The cross-pollination at the two study sites showed the greatest increase of fruit set; the progenies that presented the highest number of flowers and fruits were those of the Non x Hel and Alc x Hel crosses. The pollen viability from the two sites was extremely low and atypical for the species. For the fruit growth, cross pollination was the one that presented the greatest length and diameter of fruits. As for phenology, the flowering was advanced by one month at the two sites compared with data from the place where the progenies originated. This set of results aimed to assist the selection of superior genotypes of feijoa, correlated with their adaptability to southwestern Paraná.